Perturbative pomeron vertices and the conformal bootstrap - Ewerz, Carlo (International journal of modern physics. A, Particles and fields, gravitation, cosmology, 2016)
High energy scattering processes in QCD can be described in terms of interacting pomerons. Vertices for the interaction of pomerons have been derived in perturbative QCD. Their properties hint at the existence of a 2+1-dimensional conformal field theory of interacting pomerons. Here we study in particular the 1-to-2 and the 1-to-3 pomeron vertex and find them to be related to each other by a conformal bootstrap relation.
Gesehen am 19.11.2020